Peningkatan Kesadaran Kesehatan Metabolik dan Skrining Kolesterol Untuk Mencegah Penyakit Kardiovaskular pada Usia Produktif - Martin, Alfianto; Santoso, Alexander Halim; Gunaidi, Farell Christian; Raharjo, Budiarjo Notonagoro; Hardjanto, Kevin Angga (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2025)
Dyslipidemia is a major public health risk factor for cardiovascular disease. This condition is characterized by abnormal blood lipid levels, including LDL cholesterol, HDL cholesterol, and triglycerides. Hypercholesterolemia is often asymptomatic, resulting in many undiagnosed cases until cardiovascular complications occur. The rising prevalence of dyslipidemia, especially in low- and middle-income countries, underscores the importance of screening and prevention to reduce the risk of long-term complications. This community service activity involved 49 adult participants in Danau Sunter, North Jakarta, with cholesterol and HDL level screening conducted through blood tests by trained health workers. The results showed that 29 participants (59.18%) had abnormal cholesterol levels, and 22 participants (44.9%) had low to very low HDL levels. Adopting a healthy lifestyle, including a balanced diet, increased physical activity, and controlling other risk factors such as smoking and alcohol consumption, can help lower cholesterol levels. Routine cholesterol screening is highly effective for early detection of dyslipidemia risk, enabling timely preventive interventions to reduce cardiovascular morbidity and mortality.